Fisioterapia respiratoria y su relación con la epoc en adultos mayores del IESS, mayo- septiembre 2019. - Quinto Rivera, Joselin Lilibeth (2019)
COPD is a pathology characterized by causing a deterioration of the optimal functions of the ventilatory system, mainly there are two conditions that contribute to the development of COPD, which are chronic bronchitis and pulmonary emphysema, so it is vital to apply The physiotherapy procedures will help the patient to improve the gas exchange as well as the restoration of the health of the respiratory system. The general objective of this work is to determine the relationship between respiratory physiotherapy with Chronic Obstructive Pulmonary disease in adults. older than the IESS Hospital of Babahoyo during the period of May-September 2019, the methods applied were synthesis and deductive; The modality chosen is quantitative by the project data and the type of Research was Descriptive and Correlational, the main techniques and instruments that were used were the survey through a form applied to patients with this disease, having as a result that The respiratory physiotherapeutic procedures that COPD patients have received most are percussion and vibration followed by postural drainage. People stated that they are exposed to risk factors, with wood smoke being one of the main factors, another notable cause is that patients with This pathology has been consumers or they have been in contact with smoking and other aspects that most affect them in their health is that they sometimes go to the IESS Hospital for the treatment of their disease. It can be concluded that thanks to the application of respiratory physiotherapeutic procedures, the health of the COPD patient is restored.